2003
DOI: 10.1034/j.1600-0455.2003.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal Papillary Mucinous Tumors of the Pancreas. Comparison of helical CT and MR imaging

Abstract: MR imaging was equal or slightly superior to thin-section helical CT in the evaluation of intraductal papillary mucinous tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
3
29
1
4
Order By: Relevance
“…Large tumor size and marked dilation of the MPD in branch duct IPMNs have also been reported to be associated with malignancy [14,[20][21][22][23][24][25], but this conclusion was not confirmed by other studies [4,18,24,[26][27][28]. In the present study, both maximal MPD diameter and size of the entire cystic lesion were larger in malignant than in benign lesions, but this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Large tumor size and marked dilation of the MPD in branch duct IPMNs have also been reported to be associated with malignancy [14,[20][21][22][23][24][25], but this conclusion was not confirmed by other studies [4,18,24,[26][27][28]. In the present study, both maximal MPD diameter and size of the entire cystic lesion were larger in malignant than in benign lesions, but this difference was not statistically significant.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, minimally invasive or noninvasive imaging methods for diagnostic and preoperative examinations would be advantageous for patients and surgeons. Fukukura et al [11] reported that papillary proliferation ( > _ 3 mm) was detected equally well by helical CT and MRCP. However, in our experience, the CT and MRCP techniques often detect only a thickened septum and have difficulty detecting intramural nodules due to the limited spatial resolution of the typically small, flat tumor.…”
Section: Discussionmentioning
confidence: 99%
“…3). MR imaging is used increasingly because of its ability to determine if there is involvement of the main pancreatic duct [24]. Ultrasonography whether performed transabdominally or intraoperatively is generally not helpful [25].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…The multidetector row CT is about 80% accurate for discriminating a nonmucinous from a mucinous cyst, and for predicting malignancy. 20 MRI and MRCP have inherently superior soft tissue contrast over CT that facilitates 20,[37][38][39] Despite these advances in CT and MRI, reliable image diagnosis of pancreatic cysts is not always possible because of considerable morphological overlap in various cyst subtypes, especially small (<3 cm) cysts. As such, a classification system of cyst morphology has recently been proposed for assessing the risk of malignancy.…”
Section: Role Of Imaging In Pancreas Cyst Evaluationmentioning
confidence: 99%